Utilization of AVL with OLS on students’ motivation and common misconceptions in cell division - Ecle, Erniel Ghrizcer G.; Barquilla, Manuel B. (Journal of Education and Learning (EduLearn), 2026)
COVID-19 pandemic exhausted the learning resources in the educational system of the Philippines. This situation called for learning materials to supplement the teaching-learning process while in distance education. Hence, this paper utilized asynchronous video lectures (AVL) infused with online learning simulators (OLS) to supplement learning approaches in teaching cell division. Specifically, the goal of this study is to asses the students’ motivation as well as their common misconceptions in learning cell division. Using students’ motivation towards science learning (SMTSL) questionnaire, it was found that the learners are moderately motivated in general and are low to highly-motivated in other areas considered. These results may be associated to the absence of teacher and student interaction. Using the relational and structural scoring of concept maps, it was found that the concept map scores of the learners before and after the use of AVL with OLS were found to be significant. This implies that the misconception of the learners has significantly improved. With this, the AVL with OLS can be utilized as a learning supplement to teach cell division with recorded moderate levels of motivation among learners as well as the significant improvement in the misconceptions among them. Nonetheless, more improvements may be applied to boost the motivation levels among learners.